2009
DOI: 10.1111/j.1464-5491.2009.02772.x
|View full text |Cite
|
Sign up to set email alerts
|

A proof‐of‐concept study of the effectiveness of a removable device for offloading in patients with neuropathic ulceration of the foot: the Ransart boot

Abstract: Time to healing and incidence of amputation were comparable with those previously reported for non-removable devices. Given that a removable device is much more acceptable to the patient, the effectiveness, cost and acceptability of the removable devices, such as the Ransart boot, need to be compared with a non-removable device in a randomized trial. Diabet. Med. 26, 778-782 (2009).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 24 publications
(41 reference statements)
1
10
0
Order By: Relevance
“…Several non‐controlled studies show that 70–96% of plantar foot ulcers can be healed in a reasonable time frame (mean 34–79 days) with ankle‐high removable offloading shoes such as cast shoes, half‐shoes, and forefoot offloading shoes . These outcomes are comparable with those found with TCC.…”
Section: Casting and Prefabricated Healing Devicesmentioning
confidence: 78%
“…Several non‐controlled studies show that 70–96% of plantar foot ulcers can be healed in a reasonable time frame (mean 34–79 days) with ankle‐high removable offloading shoes such as cast shoes, half‐shoes, and forefoot offloading shoes . These outcomes are comparable with those found with TCC.…”
Section: Casting and Prefabricated Healing Devicesmentioning
confidence: 78%
“…Several noncontrolled studies show that 70% to 96% of plantar foot ulcers can be healed in a reasonable time frame (mean 34‐79 d) with ankle‐high removable offloading devices, provided they are used regularly . Multiple cross‐sectional studies also consistently found that a variety of removable ankle‐high offloading devices were more effective in reducing plantar pressure at the forefoot than a variety of footwear interventions (custom‐made, therapeutic, extra‐depth, conventional, or standard footwear) .…”
Section: Recommendationsmentioning
confidence: 99%
“…Half-shoes, forefoot off-loading shoes, and cast shoes may be effective in healing neuropathic forefoot ulcers (healing proportions, 58%-91%), although their efficacy requires confirmation in prospective trials. 34,[51][52][53][54] Conventional or standard therapeutic footwear is not effective in ulcer healing, and the role of custom footwear in this context is not yet clear. 55 Several prospective controlled studies have shown that surgical interventions such as Achilles tendon lengthening, metatarsal-phalangeal joint arthroplasty, and metatarsal head resection may have only limited additional value in ulcer healing compared with conservative treatment.…”
Section: The Evidence Base: What Work and What Does Not Work?mentioning
confidence: 99%